Teacher questions, wait time, and student output in classroom interaction in EMI science classes: An interdisciplinary view - An, Jiangshan; Childs, Ann (Studies in Second Language Learning and Teaching, 2023)
Past research has often shown a lack of student output in English medium instruction (EMI) classes (e.g., An et al., 2021; Lo & Macaro, 2012) and this study seeks to identify possible reasons. Guided by literature on wait time (Rowe, 1986) and teacher higher-order thinking questions (Chin, 2007), this study explores whether these two pedagogical moves have the same impact on classroom interaction in EMI science classes. 30 EMI science lessons were recorded from seven EMI high school programs in China, taught by 15 native speakers of English to homogenous groups of Chinese students. Correlation tests showed that when there was more wait time after a teacher question, the students produced lengthier responses with more linguistic complexity, took up more talk time, and asked more questions. However, greater use of teacher higher-order thinking questions, coded by Chin’s (2007) framework of constructivist questions, did not correlate with any student output measures. This suggests that wait time may be a more effective factor leading to more student output in EMI classes than asking higher-order thinking questions. Qualitative analysis showed teachers’ follow-up moves may have also played a role in the limited success of higher-order thinking questions.